Influence of Polymer Waste (Polyethylene Terephthalate) in Composites Structure Materials - Mohd Daud, Mohd Ahadlin (Center for Enhancing Knowledge (CEK), UK, 2012)
Nowadays the use of insulation wall in building construction faces some problems such as having high weight, very reflective sound, heat transfer (the effectiveness of heat conductivity) incompetent and mechanical properties (strength) limited. The sounds which impinge the wall cannot be absorbed efficiently but instead gives high reflection. This causes some noise on high echo in a room. So a good acoustic insulation must be efficient in absorbing the sound. This project proposes lightweight concrete as a replacement for insulation wall. This lightweight concrete will be developed using thermoplastic polymer waste which is recycle plastic bottles, sand, water, and cement. This research was used thermoplastic polymer waste which is PET (Polyethylene Terephthalate) material as the reinforcement material to replace small gravel in lightweight concrete. All its composition percentage of raw materials was divided into different samples composition. Its composition determines the performances of the samples in thermal conductivity coefficient, density, porosity and mechanical properties (strength and bending performance).